Leptin and insulin act on POMC neurons to promote the browning of white fat - Dodd, Garron (Cell, 2015)
The primary task of white adipose tissue (WAT) is the storage of lipids. However, ‘beige’ adipocytes also exist in WAT. Beige adipocytes burn fat and dissipate the energy as heat, but their abundance is diminished in obesity. Stimulating beige adipocyte development, or WAT browning, increases energy expenditure and holds potential for combating metabolic disease and obesity. Here we report that insulin and leptin act together on hypothalamic neurons to promote WAT browning and weight loss. Deletion of the phosphatases PTP1B and TCPTP enhanced insulin and leptin signaling in proopiomelanocortin neurons and prevented diet-induced obesity by increasing WAT browning and energy expenditure. The co-infusion of insulin plus leptin into the CNS or the activation of proopiomelanocortin neurons also increased WAT browning and decreased adiposity. Our findings identify a homeostatic mechanism for coordinating the status of energy stores, as relayed by insulin and leptin, with the central control of WAT browning.